Streptococcus mutans Growth and Resultant Material Surface Roughness on Modified Glass Ionomers - Mulder, Riaan; Maboza, Ernest; Ahmed, Rukshana (Frontiers in Oral Health, 2020)
The present study investigate the optical density of Streptococcus Mutans (S. mutans) at 450 nm (OD450 nm) as well as the change in surface roughness of three commercially available chitosan- and nanodiamond-modified glass ionomers. The results indicated that the optical density of S. mutans OD450 nm decreased significantly (p < 0.0001) from 0 hours through 2 hours to 4 hours for each of the control materials. The lowest S. mutans OD450 nm was noted for Fuji IX followed by Ketac Universal. Riva Self Cure had the largest increase in the S. mutans OD450 nm. The control materials and their chitosan / nanodiamond modifications showed significant growth at 6 hours compare to the preceding time periods of 2 and 4 hours. The materials Fuji IX, Fuji IX modified with 5% Nanodiamonds, Fuji IX modified with 10% Chitosan and Ketac Universal modified with 10% Chitosan performed the best with regard to the bacterial reduction. Only the chitosan modifications showed an increase in the surface roughness after 24 hours of exposure to the S. mutans. The chitosan and the nanodiamond modifications provided the best disruption of the S. mutans biofilm formation.